(untitled) (Baghdad Science Journal, 2007)
The effect of gamma radiation at the doses (0 , 5 , 10 or 15 ) Gray on the callus of four Triticum aestivum immature embryos genotypes (AL-Hashmiya , AL-Noor AL-Zahraa and AL-Mellad ) were studied . The fresh and dry weight for callus and shoot tips beside numbers and lengths of the shoots were used as indicators after 8 weeks . Results revealed that (AL-Noor and AL-Zahraa ) was superior by giving highest fresh and dry weight reached 274.2 and 269.2 mg and 26 and 24.3 mg respectively as compared with AL-Hashmiya and AL-Mellad. Moreover, the control treatment and the dose 10 Gray gave highest fresh weight reached 277.4 and 259.1 mg while the dry weight was highest in the control treatment and the dose 5 Gray. addition 10 Gray dose was superior to give highest rate for the number , length , fresh and dry weight of shoots reached 9.7 shoots , 3.6 cm length , 410.2 and 47.9 mg on respectively.